Altered ratios of pro- and anti-angiogenic VEGF-A variants and pericyte expression of DLL4 disrupt the vascular maturation in infantile haemangioma - Ye, Xi; Abou-Rayyah, Yassir; Bischoff, Joyce; Ritchie, Alison; Sebire, Neil J.; Watts, Patrick; Churchill, Amanda J.; Bates, David O. (Wiley Blackwell, 2016)
Infantile haemangioma (IH), the most common neoplasm in infants, is a slowly resolving vascular tumour. Vascular endothelial growth factor A (VEGF-A), which consists of both the pro- and anti-angiogenic variants, contributes to the pathogenesis of IH. However, the roles of different VEGF-A variants in IH progression and its spontaneous involution is unknown. Using patient derived cells and surgical specimens, we showed that the relative level of VEGF-A165b was increased in the involuting phase of IH and the relative change in VEGFA isoforms may be dependent on endothelial differentiation of IH stem cells. VEGFR signalling regulated IH cell functions and VEGF-A165b inhibited cell proliferation and the angiogenic potential of IH endothelial cells in vitro and in vivo. The inhibition of angiogenesis by VEGF-A165b was associated with the extent of VEGF receptor 2 (VEGFR2) activation, degradation and Delta Like Ligand 4 (DLL4) expression. These results indicate that VEGF-A variants can be regulated by cell differentiation and are involved in IH progression. We also demonstrated that DLL4 expression was not exclusive to the endothelium in IH but was also present in pericytes, where the expression of VEGFR2 is absent, suggesting that pericyte-derived DLL4 may prevent sprouting during involution independently of VEGFR2. Angiogenesis in IH may therefore appears to be controlled by DLL4 within the endothelium in a VEGF-A isoform dependent manner, and in perivascular cells in a VEGF independent manner. The contribution of VEGF-A isoforms to disease progression also indicates that IH may be associated with altered splicing.